Cholesterol metabolism is a potential therapeutic target in Duchenne muscular dystrophy. Issue 3 (26th May 2021) - Amor, Fatima; Vu Hong, Ai; Corre, Guillaume; Sanson, Mathilde; Suel, Laurence; Blaie, Stephanie; Servais, Laurent; Voit, Thomas; Richard, Isabelle; Israeli, David
Abstract: Background: Duchenne muscular dystrophy (DMD) is a lethal muscle disease detected in approximately 1:5000 male births. DMD is caused by mutations in the DMD gene, encoding a critical protein that links the cytoskeleton and the extracellular matrix in skeletal and cardiac muscles. The primary consequence of the disrupted link between the extracellular matrix and the myofibre actin cytoskeleton is thought to involve sarcolemma destabilization, perturbation of Ca 2+ homeostasis, activation of proteases, mitochondrial damage, and tissue degeneration. A recently emphasized secondary aspect of the dystrophic process is a progressive metabolic change of the dystrophic tissue; however, the mechanism and nature of the metabolic dysregulation are yet poorly understood. In this study, we characterized a molecular mechanism of metabolic perturbation in DMD. Methods: We sequenced plasma miRNA in a DMD cohort, comprising 54 DMD patients treated or not by glucocorticoid, compared with 27 healthy controls, in three groups of the ages of 4–8, 8–12, and 12–20 years. We developed an original approach for the biological interpretation of miRNA dysregulation and produced a novel hypothesis concerning metabolic perturbation in DMD. We used the mdx mouse model for DMD for the investigation of this hypothesis. Results: We identified 96 dysregulated miRNAs (adjusted P ‐value <0.1), of which 74 were up‐regulated and 22 were down‐regulated in DMD. We confirmed the dysregulation in DMD of Dystro‐miRs, Cardio‐miRs, and a large number of the DLK1‐DIO3 miRNAs. We also identified numerous dysregulated miRNAs yet unreported in DMD. Bioinformatics analysis of both target and host genes for dysregulated miRNAs predicted that lipid metabolism might be a critical metabolic perturbation in DMD. Investigation of skeletal muscles of the mdx mouse uncovered dysregulation of transcription factors of cholesterol and fatty acid metabolism (SREBP‐1 and SREBP‐2), perturbation of the mevalonate pathway, and the accumulation of cholesterol in the dystrophic muscles. Elevated cholesterol level was also found in muscle biopsies of DMD patients. Treatment of mdx mice with Simvastatin, a cholesterol‐reducing agent, normalized these perturbations and partially restored the dystrophic parameters. Conclusions: This investigation supports that cholesterol metabolism and the mevalonate pathway are potential therapeutic targets in DMD.